Images Representation Using Compact Quadtree Traversal Coding Technique (مجلة المنصور, 2023)
A quadtree structure is a spatial data structure and considered as one of the most important hierarchical techniques for representing digital images that attempt to save storage by aggregation data that have similar or identical values into blocks considered as quadtree nodes. Quadtree traversal is a pointerless technique (called implicit quadtree) which represent image in the form of preorder traversal of the quadtree nodes. It is a listing of all the node colors in the order given by the preorder traversal (depth first traversal) of the tree, which is more efficient in storage saving and fast retrieving and transmitting image. In this paper a new compact quadtree traversal coding was introduced that based on merging between a quadtree traversal technique and run length code technique that is used in image representation.